Geographical information ranges: conceptualising holistic information landscapes - Kaitlin E. Montague (Information Research: An International Electronic Journal)
Introduction. As unsheltered homelessness is growing in the United States (US), the habitation of vehicles as an affordable housing option is increasing. Policies continue to criminalise and marginalise vehicle residents, pushing them farther away from essential information resources. This study investigates vehicle residency from an information access perspective.